Big Data in Organizations and the Role of Human Resource Management - M. Scholz, Tobias (Personalmanagement und Organisation, 2017)
Big data are changing the way we work. This book conveys a theoretical understanding of big data and the related interactions on a socio-technological level as well as on the organizational level. Big data challenge the human resource department to take a new role. An organization's new competitive advantage is its employees augmented by big data.